2022
DOI: 10.1093/hr/uhac105
|View full text |Cite
|
Sign up to set email alerts
|

DgbZIP3 interacts with DgbZIP2 to increase the expression ofDgPODfor cold stress tolerance in chrysanthemum

Abstract: The bZIP transcription factor plays a very important role in abiotic stresses for instance drought, salt, and low-temperature stress, but the mechanism of action at low temperature is still unclear. In this study, overexpression of DgbZIP3 led to increased whereas antisense suppression of DgbZIP3 resulted in decreased tolerance of chrysanthemum (Chrysanthemum morifolium Ramat.) to cold stress. Electrophoretic mobility shift assay (EMSA), chromatin immunoprecipitation (ChIP), luciferase complementary imaging an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…We proposed that the co-activators could stimulate the DNA binding activity of their interacting partner without altering the mobility of the complex in the EMSA assays due to their unstable binding to the complex. Similar results were also found in previous studies, which reported that co-activator protein might enhance the DNA binding activity of target DNA without binding stably to the complex (Després et al, 2000;An et al, 2021;Bai et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…We proposed that the co-activators could stimulate the DNA binding activity of their interacting partner without altering the mobility of the complex in the EMSA assays due to their unstable binding to the complex. Similar results were also found in previous studies, which reported that co-activator protein might enhance the DNA binding activity of target DNA without binding stably to the complex (Després et al, 2000;An et al, 2021;Bai et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…The ability of bZIP transcription factors to enhance plant tolerance to abiotic stress has been extensively reported; for example, in chrysanthemum, overexpression of DgbZIP3 and DgbZIP2 increases cold tolerance. Interestingly, DgbZIP3 and DgbZIP2 can also interact to regulate the expression of DgPOD , which can improve the tolerance of chrysanthemum to cold stress by promoting the increase of peroxidase activity and regulating the balance of reactive oxygen species ( Bai et al., 2022 ). Overexpression of GmbZIP2 in A.thaliana and soybean hairy roots can improve plant tolerance to salt and drought stress, and significantly increased expression of the soybean stress-responsive genes GmDHN15 , GmMYB48 , GmLEA , and GmWD40 is detected in transgenic hairy roots ( Yang et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of the bZIP TFs, DgbZIP3 and DgbZIP2 increased cold tolerance in chrysanthemum. DgbZIP3 interacted with another TF, DgbZIP2 , which further regulated the expression of DgPOD , thereby reducing ROS accumulation and increasing tolerance [ 167 ]. Tian et al (2022) identified and characterized 23 TCP TF genes in C. nankingense , and the expression profiles of these CnTCP genes were downregulated under cold stress [ 168 ].…”
Section: Abiotic Stress Tolerancementioning
confidence: 99%